Development of a digital maturity model for small and medium sized enterprises :|a case study in Turkey - Yıldız, Sedanur. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2021., 2021)
SMEs play an immense role in the value chain and their daily operations are relatively more flexible than larger companies due to their smaller sizes and existence of less bureaucracy in their operations. SMEs are recognized by their high product customization skills. However, there are many obstacles that SMEs have in their DX maturity advancements such as financial and technical insufficiencies, organizational drawbacks, issues with standardizations and lack of alliances with research institutions. Given these distinct characteristics the DX maturity of SMEs should be evaluated accordingly by considering the challenges they face. The aim of this study is to develop a valid and reliable digital maturity model for SMEs and to implement this framework to analyze the factors that affect the digitalization levels of these companies. The DX assessment survey D3A is developed with the special focus on SMEs and the restrictions on their DX journeys. The generated framework is applied on 100 SMEs by face-to-face interviews and the results are analyzed. Valuable contributions are made to the DX literature by showing that D3A is a reliable and valid framework that can be used in assessing the DX maturity of SMEs. Furthermore, insights are generated on the factors that affect the digitalization levels of SMEs. These findings can be effectively used by the SMEs to generate critical improvement directions in developing their DX roadmaps. Nevertheless, D3A framework provides a general understanding of the digital maturity of SMEs in our area.
Keywords: Small business -- Turkey.; Digital communications -- Small business.